Effect of marital status on patient-reported outcomes following total hip arthroplasty: a matched analysis with minimum 2-year follow-up. Issue 3 (May 2021) - Lall, Ajay C; Schwarzman, Garrett R; Battaglia, Muriel R; Chen, Sarah L; Maldonado, David R; Domb, Benjamin G
Introduction: Mental health and patient expectation have been identified as key predictors of recovery following THA; however, there is limited literature examining the effects of social support and marital status on patient-reported outcomes (PROs). Methods: Data were prospectively collected and retrospectively reviewed for patients who underwent THA between July 2008 and January 2016. Patients were included if they underwent primary THA during this period and if they had documented preoperative marital status of married, divorced, or never married. Married patients were group matched to non-married patients (divorced or never married) with similar sex, age, body mass index (BMI), gender distribution, and frequency of surgical approach. Results: There were 414 married patients and 98 non-married patients who were eligible and had minimum 2-year follow-up. Mean PROs were significantly worse in the non-married group than the married group for the following measures: modified Harris Hip Score ( p = 0.002), Harris Hip Score ( p = 0.002), Forgotten Joint Score ( p = 0.04), and the physical portions of the Veterans RAND ( p = 0.025) and Short Form ( p = 0.02) surveys. Conclusions: Our study demonstrated inferior absolute PRO scores at latest follow-up for patients who were non-married compared to married following THA. These results show that while total hip replacement may still yield clinical benefit in all patients, non-married patients may ultimately achieve an inferior functional status, and expectations should be adjusted accordingly. Physicians should assess levels of psychosocial support in their patients prior to undergoing hip arthroplasty in order to optimise results.